(NmSTISLAW rOSTROPOWI^ ~AST_ (B1s (NwEHI VIZNENNOGO I TWOR^ESKOGO PUTIs - (Nm(B.(NsPEKTORs ((NtARBUTs (NiERSALIMs, 1997)
(NpAMQTI MOIH RODITELEJ aLEKSANDRA iZRAILEWI^A sPEKTORA I mARII mIHAJLOWY bUR[TEJN(B.s
Keywords: (NMONOGRAFIQs